2018
DOI: 10.1016/j.ajpath.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Autophagy in Nlrp3 Inflammasome Activation and Medial Thickening of Mouse Coronary Arteries

Abstract: We hypothesized that autophagy and associated lysosome function serve as a critical modulator during Nod-like receptor family pyrin domain containing 3 (Nlrp3) inflammasome activation on proatherogenic stimuli. We first demonstrated that 7-ketocholesterol stimulated Nlrp3 inflammasome formation and activation as shown by increased colocalization of inflammasome components [Nlrp3 versus apoptosis associated speck-like protein (Asc) or caspase-1] and enhanced cleavage of caspase-1 into active caspase-1 to genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Furthermore, it has been reported that metformin activates autophagy via SIRT1 53 , and that SIRT1 could modulate the inhibition of NLRP3 inflammasome activation 54,55 . Considering the evidence that AMPK, SIRT1 and autophagy are coordinately regulated 56 , and that autophagy induction negatively regulates NLRP3 inflammasome activation [57][58][59] , there is a possibility that autophagy through AMPK and SIRT1 activation may be involved in the lowered caspase-1 protein expression induced by metformin, contributing to the inhibition of NLRP3 activation and IL-1β secretion (mature IL-1β); however, to demonstrate this, further studies are required. Recently, the IL-1β-IL-1R signalling pathway controlled by NLPR3 inflammasome has been reported to play a critical role in the pathogenesis of psoriasis in humans and induced by IMQ in mice 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that metformin activates autophagy via SIRT1 53 , and that SIRT1 could modulate the inhibition of NLRP3 inflammasome activation 54,55 . Considering the evidence that AMPK, SIRT1 and autophagy are coordinately regulated 56 , and that autophagy induction negatively regulates NLRP3 inflammasome activation [57][58][59] , there is a possibility that autophagy through AMPK and SIRT1 activation may be involved in the lowered caspase-1 protein expression induced by metformin, contributing to the inhibition of NLRP3 activation and IL-1β secretion (mature IL-1β); however, to demonstrate this, further studies are required. Recently, the IL-1β-IL-1R signalling pathway controlled by NLPR3 inflammasome has been reported to play a critical role in the pathogenesis of psoriasis in humans and induced by IMQ in mice 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the slides were cleared and mounted with DPX. Image-Pro Plus 6.0 software (Rockvile, MD, USA) was used to calculate the area percentage of the positive staining [71].…”
Section: Immunohistochemical Analysesmentioning
confidence: 99%
“…The rate of co-localization of Lamp-1 with RAB7, ALG-2, VPS16 in the aortic medial SMCs was expressed by Pearson's Correlation Coefficient (PCC) using Image-Pro Plus 6.0 software (Media Cybernetics, Bethesda, MD, USA). PCC is determined by correlation coefficient, r (r = −1 to 0), as mentioned previously [71,72].…”
Section: Immunofluorescent Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we show that the levels of p62/sqtsm1 and LC3II, as well as the levels of NLRP3, caspase1, and IL-1β, increased after treatment with bafA1, thereby confirming that the activation of NLRP3 inflammatory corpuscles may be related to the intracellular accumulation of p62. Additionally, in vivo experiments have shown that inhibition of lysosomal function enhances the formation and activation of NLRP3 inflammatory bodies [35]. Alternatively, pyroptosis has also been reported to have a regulatory role in autophagy.…”
mentioning
confidence: 99%